Die Geschichtlichkeit der Translation(swissenschaft): Zur paradigmatischen Relevanz der maschinellen Übersetzung - Rozmyslowicz, Tomasz (chronotopos – A Journal of Translation History, 2020)
Although machine translation has become an everyday and ubiquitous phenomenon, it has met with widespread disinterest in translation studies. The essay attempts to show that this is no coincidence, but can be explained by the history of translation studies itself. It is claimed that in the transition from the paradigm of 'recoding' to the paradigm of 'action', which at the same time marks the emancipation of translational studies from linguistics, machine translation falls into a systematically generated blind spot: The guiding idea of a translating human subject inevitably leads to the suppression of machine translation, whose increasing social relevance in turn puts this guiding idea under empirical pressure. The article suggests that the challenge posed by machine translation for a discipline focused on human translation should be met by recognizing the constitutive historicity of translation.